The Impact of Board of Directors and Islamic Shariah on Company Internal Control: Evidence from Jordan - Amayreh, Ibrahim; Ananzeh, Husam; Bugshan, Abdullah (International Journal of Economics and Financial Issues, 2024)
The purpose of this paper is to examine the impact of corporate governance and compliance with Shariah on internal controls over financial reporting. It also examines the moderating role of Shariah compliance on the relationship between corporate governance structures and internal reporting controls. Ordinary least square (OLS) models are applied to 94 listed Jordanian companies on Amman Stock Exchange over the period 2015-2021. The empirical evidence shows board size, board meetings, Shariah compliance, and auditor type have a negative impact on material weaknesses in internal controls (MWIC). Second, unitary leadership, where the same individual is both the chair and CEO, is positively correlated to MWIC. Third, Shariah compliance strengthens the effect of board meetings, suggesting that Shariah compliance and good corporate governance mechanisms reinforce each other to ensure higher-quality internal financial reporting controls.